Anatomy and physiology of the blood–brain barrier. (February 2015) - Serlin, Yonatan; Shelef, Ilan; Knyazer, Boris; Friedman, Alon
Abstract: Essential requisite for the preservation of normal brain activity is to maintain a narrow and stable homeostatic control in the neuronal environment of the CNS. Blood flow alterations and altered vessel permeability are considered key determinants in the pathophysiology of brain injuries. We will review the present-day literature on the anatomy, development and physiological mechanisms of the blood–brain barrier, a distinctive and tightly regulated interface between the CNS and the peripheral circulation, playing a crucial role in the maintenance of the strict environment required for normal brain function.